2016
DOI: 10.1002/app.44099
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the surface properties of polybenzoxazines: Interaction of polybenzoxazine model compounds with metal ions and water

Abstract: The structure of polybenzoxazines (and their properties) is mainly defined by the existence of intra-and intermolecular hydrogen bonds. The effect of different substituents present in the phenolic ring of polybenzoxazines can modulate these intermolecular forces and the interaction with other materials, such as metals. To extend this knowledge, a series of structure-controlled polybenzoxazines and polybenzoxazine model compounds have been synthesized. The interactions with different metal ions have been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…However, it was observed that the CH 2  groups signal shifts downfield when the metal ions were added. This was attributed to “the reduction of electron density of the methylene group as a result of the coordination of the metal ion with the dimer” which is consistent with the structure presented in Scheme c. Moreover, in the case of Zn 2+ , a broad peak was detected, while the splitting of the CH 2  signal was observed when Cu 2+ and Al 3+ were utilized.…”
Section: Spatial Conformationsupporting
confidence: 77%
See 4 more Smart Citations
“…However, it was observed that the CH 2  groups signal shifts downfield when the metal ions were added. This was attributed to “the reduction of electron density of the methylene group as a result of the coordination of the metal ion with the dimer” which is consistent with the structure presented in Scheme c. Moreover, in the case of Zn 2+ , a broad peak was detected, while the splitting of the CH 2  signal was observed when Cu 2+ and Al 3+ were utilized.…”
Section: Spatial Conformationsupporting
confidence: 77%
“…The spatial conformation of polybenzoxazines is key for the polybenzoxazine capability of acting as a ligand to metal ions due to the presence of intramolecular hydrogen bonding. In 2016, Shen et al . studied the influence of the spatial conformation over the interaction between polybenzoxazines and metal ions by synthesizing a significant number of dimers with aliphatic and aromatic amines as well as with electron donating and withdrawing substituents in the phenolic portions (see Scheme ).…”
Section: Spatial Conformationmentioning
confidence: 99%
See 3 more Smart Citations